Assessment of the application for renewal of the authorisation of Natuphos (3‐phytase) as a feed additive for poultry and pigs. (2nd April 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Natuphos ® is a feed additive that contains 3‐phytase which is produced by a genetically modified strain of Aspergillus niger . The product is currently authorised for use as a feed additive in chickens for fattening, piglets (weaned) and pigs for fattening, laying hens and turkeys for fattening, ducks, sows, all minor avian species other than ducks and ornamental birds. This scientific opinion concerns the renewal of the authorisation of this additive for those species. The application also included chickens reared for laying/breeding, turkeys reared for breeding and breeding hens. The applicant provided evidence that the additive in the market complies with the conditions of authorisation. According to the information provided by the applicant, no new evidence has been identified that would make the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) reconsider the previous conclusions regarding the safety for the target species, consumer and environment under the authorised conditions of use. The additive is a respiratory sensitiser and a potential skin sensitiser. The present application for renewal of the authorisation does not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive. Therefore, there was no need for assessing the efficacy of the additive in for those species for which an authorisation exists. The Panel also considered that the additive is safe and has a potential to be efficacious in chickens reared for laying/breeding, turkeys reared for breeding, breeding hens and suckling piglets at the corresponding recommended doses.